The piano in chamber ensemble : an annotated guide - Hinson, Maurice; Roberts, Wesley (Indiana University Press, 2021)
Keyboard, string, woodwind, brass, and percussion players and teachers will find a wealth of chamber works from all periods in this invaluable guide.